On network coding in wireless ad-hoc networks. (13th February 2007) - Zhang, Jingyao; Fan, Pingyi
Network coding has been shown to be an effective way to achieve the maximum flow capacity of network. In this work, we will study this technique on wireless Ad-Hoc networks. To reduce the cost and complexity, we propose a modified Ford-Fulkerson algorithm to obtain the maximum flow and encoding nodes in a network. We also find a Conflict Phenomenon in undirected networks that cannot be solved by network coding. Furthermore, we will show that the maximum flow value from a source to a destination is approximately Poisson distributed, and the number of encoding nodes is close to geometric distribution.